Peningkatan Pengetahuan Siswa tentang Kesadaran Ekologis untuk Lingkungan Berkelanjutan di SMA Negeri 1 Pinrang - Ridwan Syam; Atma Ras; Hariashari Rahim (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Enhancing ecological awareness among students is a crucial step towards achieving a sustainable environment. This community service activity aims to increase the knowledge of students at SMA Negeri 1 Pinrang about the importance of ecological awareness and how they can contribute to environmental preservation. Through a series of structured activities including pre-tests, interactive discussions, and post-tests, students are provided with an in-depth understanding of critical environmental issues such as climate change, natural resource conservation, and waste management. The program also includes practical workshops that allow students to apply their knowledge in small-scale environmental projects within the school environment. The results of this activity are expected to foster environmental awareness and responsibility among students, as well as encourage them to implement sustainable practices in their daily lives. Program evaluation shows a significant improvement in students' understanding and positive attitudes towards environmental conservation efforts. There is evidence of behavior changes supporting sustainability among the majority of participants. Furthermore, student initiatives in proposing and leading environmental projects at school have increased substantially after the program. This activity is expected to serve as a model for other schools in developing effective and sustainable environmental education programs, as well as encouraging collaboration between educational institutions and local communities in environmental conservation efforts.